2021
DOI: 10.3389/fimmu.2021.735014
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of STAT6 Ameliorates Myeloid Fibroblast Activation and Alternative Macrophage Polarization in Renal Fibrosis

Abstract: A hallmark of chronic kidney disease is renal fibrosis, which can result in progressive loss of kidney function. Currently, there is no effective therapy for renal fibrosis. Therefore, there is an urgent need to identify potential drug targets for renal fibrosis. In this study, we examined the effect of a selective STAT6 inhibitor, AS1517499, on myeloid fibroblast activation, macrophage polarization, and development of renal fibrosis in two experimental murine models. To investigate the effect of STAT6 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…Recent studies have shown that STAT6 could suppress M2 macrophage polarization and be involved in the monocyte-to-fibroblast transition in folic acid nephropathy (33). Furthermore, STAT6-specific inhibitor (AS 1517499) has been proven to prevent M2 macrophage polarization and transformation of myofibroblasts, which lead to a reduction of collagen deposition and ECM production in the injured kidney (34). This evidence supports that JAK3/STAT6 signaling takes a crucial part in renal fibrosis via regulating the MMT.…”
Section: Regulation Of Macrophage-tomyofibroblast Transition and Infl...mentioning
confidence: 62%
“…Recent studies have shown that STAT6 could suppress M2 macrophage polarization and be involved in the monocyte-to-fibroblast transition in folic acid nephropathy (33). Furthermore, STAT6-specific inhibitor (AS 1517499) has been proven to prevent M2 macrophage polarization and transformation of myofibroblasts, which lead to a reduction of collagen deposition and ECM production in the injured kidney (34). This evidence supports that JAK3/STAT6 signaling takes a crucial part in renal fibrosis via regulating the MMT.…”
Section: Regulation Of Macrophage-tomyofibroblast Transition and Infl...mentioning
confidence: 62%
“…Our previous studies have shown that FA treatment can cause severe fibrosis and renal dysfunction of mice at the end of 14 days ( Liang et al, 2017a ; Chen et al, 2021a ; Liu et al, 2021b ). The activation of myeloid fibroblasts and transition of macrophages to myofibroblasts are proved to be critical factors that contribute to progression of kidneys fibrosis ( Jiao et al, 2021a ; Jiao et al, 2021b ; Liu et al, 2021b ). However, the molecular signaling mechanisms that trigger bone marrow-derived fibroblasts activation and promote macrophages to myofibroblasts differentiation are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow–derived fibroblast precursors express hematopoietic markers such as CD45 ( Liang et al, 2017a ). In response to persistent inflammatory stimuli, bone marrow-derived fibroblasts are activated and further differentiate into myofibroblasts ( Liang et al, 2017a ; Jiao et al, 2021a ; Jiao et al, 2021b ). Of note, STING has an important role in the regulation of bone marrow-derived macrophages activation ( Yan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, however, macrophages can also promote renal fibrosis, which is a major driver of progression to end-stage AKI. For instance, recent studies suggest that the role of M2 macrophages in chronic kidney disease may be the opposite of that in AKI, and targeting signal transducer and activator of transcription 6 (STAT6) can inhibit the polarization of M2 macrophages, thereby protecting renal function ( Jiao et al, 2021a ; Jiao et al, 2021b ). Elucidating the exact role and timing of M2 activation is thus imperative to stunt the progression of AKI.…”
Section: Introductionmentioning
confidence: 99%